2005
DOI: 10.1080/10428190400010775
|View full text |Cite
|
Sign up to set email alerts
|

Mastocytosis: Pathology, genetics, and current options for therapy

Abstract: Mast cell disorders are defined by an abnormal accumulation of tissue mast cells (MCs) in one or more organ systems. Symptoms in mastocytosis result from MC-derived mediators and, less frequently, from destructive infiltration of MCs. Cutaneous mastocytosis (CM) is a benign disease of the skin and may regress spontaneously. Systemic mastocytosis (SM) is a persistent disease in which a somatic c-kit mutation at codon 816 is usually detectable in MCs and their progenitors. The clinical course in these patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
0
17

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(187 citation statements)
references
References 108 publications
4
166
0
17
Order By: Relevance
“…However, serum tryptase levels can be transiently elevated in severe allergic reactions, as well as in patients with myeloid neoplasms. 23 Serum tryptase levels 420 ng/ml have been reported in 39% of de novo acute myeloid leukemia, 44% of secondary acute myeloid leukemia, and in patients with myelodysplastic and myeloproliferative diseases. One study reported that approximately 5% of acute myeloid leukemia cases had serum tryptase levels 4200 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, serum tryptase levels can be transiently elevated in severe allergic reactions, as well as in patients with myeloid neoplasms. 23 Serum tryptase levels 420 ng/ml have been reported in 39% of de novo acute myeloid leukemia, 44% of secondary acute myeloid leukemia, and in patients with myelodysplastic and myeloproliferative diseases. One study reported that approximately 5% of acute myeloid leukemia cases had serum tryptase levels 4200 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent publications by the same authors, the phrase concerning the validity of serum tryptase in the diagnostic work-up has been changed from 'associated myeloid disorder' to 'systemic mastocytosis with associated clonal hematologic non-mast-cell disease' which by definition includes other entities beyond myeloid disorders. 3,23 Myeloid disorders account for 80-90% of cases of systemic mastocytosis with associated clonal hematologic non-mast-cell disease myelodysplastic syndrome/myeloprolifertive disorder being most common. Of the associated lymphoid malignancies, plasma cell myeloma is most frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptase is a protease specific for and present in all mast cells, and serum levels may correlate with mast cell burden, especially after activation [1,4,13,35,38,39]. In a significant number of both children and adults with mastocytosis confined to the skin, however, the serum tryptase level may be normal (1-15 ng/mL) [13,40]. It is unclear if children whose tryptase levels remain normal should be monitored past adolescence.…”
Section: Diagnosismentioning
confidence: 99%
“…After a Gastric hypersecretion H 2 -antagonists [12,20,54,86] Proton pump inhibitors [12,86] Abdominal pain Disodium cromolyn [12,15,20,54,86] H 2 -antagonists [30,86] Glucocorticoids [12] Prostaglandin-D2 Flushing Acetylsalicylic acid b [4,43] NSAIDs b [4,43,86] Syncope Acetylsalicylic acid b [20,43] NSAIDs b [4,20,43] Heparin Hemorrhage, surgical Protamine c [3,12,90] Fibrinogen, coagulation factors c [12] Hemorrhage, gastric H 2 -antagonists [12,15] Proton pump inhibitors [12,54] Thromboxane Bronchoconstriction, vasoconstriction Antileukotrienes [30] Leukotrienes Vasoconstriction/vasodilation, increased capillary permeability Antileukotrienes [15,30] Tryptase Fibrinolysis Fresh frozen plasma c [89] Antifibrinolytics c [89] a Mast cell stabilizer hypothesized to counter effects of epinephrine b Aspirin and/or NSAIDs should be administered under controlled conditions only c Clinical efficacy unclear mastocytosis-related anaphylaxis-like incident, serum tryptase levels may return to normal but again increase as mast cell burden increases [39]. Paradoxically, children with mastocytosis, particularly those with mild disease, may have normal serum tryptase levels [35,40]…”
Section: Intraoperative Crisis Managementmentioning
confidence: 99%
See 1 more Smart Citation